2020
DOI: 10.1002/nau.24317
|View full text |Cite
|
Sign up to set email alerts
|

Two‐year safety and efficacy outcomes for the treatment of overactive bladder using a long‐lived rechargeable sacral neuromodulation system

Abstract: Aims: Sacral neuromodulation (SNM) therapy for overactive bladder (OAB) has proven long-term safety and efficacy. Historically, the only commercially available SNM device was nonrechargeable requiring replacement surgery due to battery depletion. The Axonics System is the first rechargeable SNM device and is qualified to last a minimum of 15 years in the body. The study objective was to evaluate the safety and efficacy of this rechargeable SNM system. This study reports 2-year outcomes.Methods: A total of 51 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…This analysis confirmed the effective and stable performance of both systems. The improvements in voiding diaries and subjective scores observed in both group patients are comparable to those previously reported in patients using other types of SNM devices 13 . Comparing the two systems directly, we found that there were slight differences concerning improvements in daily urination and urine leakage times.…”
Section: Discussionsupporting
confidence: 86%
“…This analysis confirmed the effective and stable performance of both systems. The improvements in voiding diaries and subjective scores observed in both group patients are comparable to those previously reported in patients using other types of SNM devices 13 . Comparing the two systems directly, we found that there were slight differences concerning improvements in daily urination and urine leakage times.…”
Section: Discussionsupporting
confidence: 86%
“…Overall, in our patient population, both short-term (94%) and long-term (76%) success rates of SNM were comparable or superior to those reported in other SNM studies, irrespective of the initial medical indication [11][12][13][14][15] . Outcomes of SNM for bladder and bowel disorders in elderly patients have also been evaluated by other studies.…”
Section: Discussionsupporting
confidence: 80%
“…A further paper about device programming settings for RELAX-OAB provided additional detail [11]. Subsequent to the initial literature search, new peer-reviewed publications [12,13] verified the content of the previously unpublished papers.…”
Section: Review Of Clinical Effectiveness Evidencementioning
confidence: 99%
“…For the discontinuation rate of the non-rechargeable system, Cedar interpreted the available data [18] to give a 5-year discontinuation rate of 17% rather than 6%. Cedar also changed the clinical inputs for rechargeable systems, to be based on studies using the rechargeable system [8][9][10][11]13] rather than data from the Insite study [17]. The probability of lead migration or fracture was changed to be constant throughout the model, meaning it was no longer occurring only in the cycle with an implantation or revision procedure.…”
Section: Changes By Cedarmentioning
confidence: 99%